By using y=2^x or otherwise, solve
4^x - 3 (2^(x+1)) + 8= o
so i understand to convert the 4^x to 2^x(2) but how to proceed ??
sorry cant type equations properly dont know what language this forums use and again sorry.
$\displaystyle \displaystyle \begin{align*} 4^x - 3 \cdot 2^{x + 1} + 8 &= 0 \\ \left( 2^2 \right) ^x - 3 \cdot 2 \cdot 2^x + 8 &= 0 \\ 2^{2x} - 6 \cdot 2^x + 8 &= 0 \\ \left( 2^x \right) ^2 - 6 \cdot 2^x + 8 &= 0 \\ X^2 - 6X + 8 &= 0 \textrm{ after making the substitution } X = 2^x \end{align*}$
You should now be able to solve.